2018
DOI: 10.1158/1541-7786.mcr-18-0212
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Resistance to EGFR-Targeted Therapy by Calcium Signaling in NSCLC Cells

Abstract: Targeted therapies against oncogenic receptor tyrosine kinases (RTK) show promising results in the clinic. Unfortunately, despite the initial positive response, most patients develop therapeutic resistance. Most research has focused on acquired resistance occurring after an extensive time of treatment; however, the question remains as to how cells can survive an initial treatment, as early resistance to apoptosis will enable cells to develop any growth-stimulating mechanism. Here, the non-small cell lung cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…They can also remain in a state of dormancy for extended periods of time, which, in conjunction with a decelerated cell cycle, enables them to acquire mutations that allow for cellular progression [ 73 ]. Research has substantiated a consistent trait of these persister cells as having increased calcium signaling in parallel with cytoskeleton remodeling [ 74 ]. Understanding the vast array of mechanisms of resistance remains crucial for future drug discovery and optimizing combination therapy.…”
Section: Calcium In Immune Evasion and Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…They can also remain in a state of dormancy for extended periods of time, which, in conjunction with a decelerated cell cycle, enables them to acquire mutations that allow for cellular progression [ 73 ]. Research has substantiated a consistent trait of these persister cells as having increased calcium signaling in parallel with cytoskeleton remodeling [ 74 ]. Understanding the vast array of mechanisms of resistance remains crucial for future drug discovery and optimizing combination therapy.…”
Section: Calcium In Immune Evasion and Drug Resistancementioning
confidence: 99%
“…Epidermal growth factor (EGF), the ligand for EGFR, was found to play a role in the calcium oscillations essential for EMT [ 87 ]. The evidence suggests that the blockage of cells from extracellular calcium via a calcium chelator known as EGTA increases the efficacy of EGFR inhibitors such as afatinib [ 74 ]. Immunotherapies are also on the rise in cancer treatment.…”
Section: Combination Therapymentioning
confidence: 99%
“…We observed that low [Ca 2+ ]e-mediated [Ca 2+ ]i oscillations were abolished by gefitinib and U73122 in PC-9/GR and PC-9 cells, suggesting that the absence of [Ca 2+ ]e led to enhanced gefitinib sensitivity and reversed gefitinib-mediated cytotoxicity and apoptosis. Mulder et al demonstrated that initial targeted therapy on PC-9 cells increases the activity of Ca 2+ signaling-related proteins and deprives the cell of extracellular Ca 2+ , which results in the marked enhancement of afatinib efficacy [12]. Our data indicated that increased [Ca 2+ ]e influx in PC-9/GR cells contributed to gefitinib resistance; therefore, restricting [Ca 2+ ]e could be key in enhancing drug sensitivity.…”
Section: Plos Onementioning
confidence: 52%
“…Notably, treatment using EGFR-targeting afatinib causes Ca 2+ signaling-related gene expression in PC-9 cells. Reduced extracellular Ca 2+ ([Ca 2+ ]e) levels increase the sensitivity of PC-9 cells to afatinib [12]. These reports strongly suggest that Ca 2+ signaling in cancer cells is significantly associated with the development of acquired drug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular Ca 2+ influx plays important roles in cell survival, cell proliferation, invasiveness [ 12 ], and the regulation of the early G1 phase of the cell cycle [ 13 ]. Mulder et al [ 14 ] reported that afatinib treatment in PC-9 cells regulates the expression of various Ca 2+ signal-mediated proteins and that the absence of extracellular Ca 2+ enhances afatinib efficacy against NSCLC cells. However, there is a lack of understanding of afatinib-mediated changes in the extracellular Ca 2+ influx and cytotoxicity according to changes in extracellular Ca 2+ influx in cells with T790M gene mutation in EGFR.…”
Section: Introductionmentioning
confidence: 99%